Czas w kulturze rosyjskiej. Uwagi wstępne .......... 9 (Czas w kulturze rosyjskiej, 2019)
TIME IN RUSSIAN CULTURE. INTRODUCTORY REMARKS The introductory article to the volume Czas w kulturze rosyjskiej. Время в русской культуре presents the diversity of attitudes towards time. Special attention is payed to culture-based notions of time. The text points out to the achievements of interdisciplinary time study (International Society for the Study of Time). The differences between quantitative and qualitative time approaches were considered. Among important taxonomies worked out in time studies the culture division based on the dominating time aspect is mentioned. The author takes into account some general ideas concerning Russian time perception (concepts developed by B. Yegorov, D. Likhachev, V.V. Ivanov, Y. Lotman, L. Gudkov). Two Russian editorial initiatives, important as far as time research is concerned, are mentioned (periodicals: “Диалог со временем: Альманах интеллектуальной истории” and „Пространство и время”).